The quick Python book - Ceder, Naomi R. (Manning Publications, 2018)
The Quick Python Book, Third Edition is a comprehensive guide to the Python language by a Python authority, Naomi Ceder . With the personal touch of a skilled teacher, she beautifully balances details of the language with the insights and advice you need to handle any task. Extensive, relevant examples and learn-by-doing exercises help you master each important concept the first time through. Whether you're scraping websites or playing around with nested tuples, you'll appreciate this book's clarity, focus, and attention to detail.